2016
DOI: 10.1002/cm.21271
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian axoneme central pair complex proteins: Broader roles revealed by gene knockout phenotypes

Abstract: The axoneme genes, their encoded proteins, their functions and the structures they form are largely conserved across species. Much of our knowledge of the function and structure of axoneme proteins in cilia and flagella is derived from studies on model organisms like the green algae, Chlamydomonas reinhardtii. The core structure of cilia and flagella is the axoneme, which in most motile cilia and flagella contains a 9 + 2 configuration of microtubules. The two central microtubules are the scaffold of the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 107 publications
3
46
0
Order By: Relevance
“…Three‐dimensional structured illumination microscopy (3D‐SIM) further revealed that Rsph9 was specifically located in the lumen formed by the 9 MT doublets, marked by acetylated tubulin (Figure E). Distributions of the Rsph9 immunofluorescence were slightly wider than those of hydin, a CP apparatus marker [Lechtreck and Witman, ; Lechtreck et al., ; Teves et al., ] (Figure E), supporting its role as an RS subunit. Consistent to the immunoblotting results (Figure B), Rsph9 was not detected in primary cilium (Figure F).…”
Section: Resultsmentioning
confidence: 84%
“…Three‐dimensional structured illumination microscopy (3D‐SIM) further revealed that Rsph9 was specifically located in the lumen formed by the 9 MT doublets, marked by acetylated tubulin (Figure E). Distributions of the Rsph9 immunofluorescence were slightly wider than those of hydin, a CP apparatus marker [Lechtreck and Witman, ; Lechtreck et al., ; Teves et al., ] (Figure E), supporting its role as an RS subunit. Consistent to the immunoblotting results (Figure B), Rsph9 was not detected in primary cilium (Figure F).…”
Section: Resultsmentioning
confidence: 84%
“…Additionally, we found two top candidates in CEU that have not been explicitly described as sweeps previously, RSPH3 and ZNF211 (both m = 1). RSPH3 encodes a radial spoke protein that is integral in the structure of 9 + 2 motile cilia across diverse cell types, including flagellated cells [Teves et al, 2016], and so selection here may be related to ancient sperm competition in humans [Leivers et al, 2014]. ZNF211 is among a diverse set of zinc-finger genes whose products are believed to participate in the inactivation of endogenous retroviruses, parasitic mobile DNA whose effects can be deleterious to their hosts [Lukic et al, 2014].…”
Section: Application To Empirical Datasetsmentioning
confidence: 99%
“…9 Previous studies on genetic mutants in model organisms have revealed genetic contributions to flagellar motility defects. 2,[10][11][12][13][14] So far, mutations in only three genes, AKAP4 (MIM: 300185), CCDC39 (MIM: 613798), and DNAH1 (MIM: 603332), have been formally identified to cause MMAF in humans. 2,3,15,16 Among them, biallelic DNAH1 mutations in MMAF have been recurrently identified across studies and account for 28%-44% of MMAF cases.…”
Section: Introductionmentioning
confidence: 99%